2013
DOI: 10.1111/trf.12369
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of prion reduction filters in decreasing infectivity of ultracentrifuged 263K scrapie‐infected brain homogenates in “spiked” human blood and red blood cells

Abstract: The use of prion-removing filters may help to reduce the risk of transfusion-transmitted vCJD. To avoid overestimation of prion removal efficiency in validation studies, it may be more appropriate to use supernates from ultracentrifugation of scrapie-infected hamster brain homogenate rather than the current standard brain homogenates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 23 publications
4
11
0
Order By: Relevance
“…This provides an effective evaluation of the efficiency with which they remove prion infectivity from blood components. Moreover, the infectivity associated with S HS was not removed by leukodepletion from whole blood and red blood cells, further confirming its soluble nature and its presumed biophysical similarity to the endogenous soluble plasma-associated infectivity [10]. This soluble S HS -associated infectivity could represent the same form of prion infectivity previously described by Gregori et al [16,17] as the portion of the TSE infectivity present in a brain spike that could not be removed during validation studies for prion removal from blood.…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations
“…This provides an effective evaluation of the efficiency with which they remove prion infectivity from blood components. Moreover, the infectivity associated with S HS was not removed by leukodepletion from whole blood and red blood cells, further confirming its soluble nature and its presumed biophysical similarity to the endogenous soluble plasma-associated infectivity [10]. This soluble S HS -associated infectivity could represent the same form of prion infectivity previously described by Gregori et al [16,17] as the portion of the TSE infectivity present in a brain spike that could not be removed during validation studies for prion removal from blood.…”
Section: Introductionsupporting
confidence: 62%
“…This close similarity of S HS to plasma enabled the recent validation of S HS as the best prion spike for validation studies on prion removal from blood-and plasma-derived products [9,10]. In fact, when used to spike manufactured human albumin and human whole blood and red blood cells, S HS was shown to be capable of mimicking the endogenous soluble infectivity of plasma or red blood cells from 263K-infected hamsters with respect to different kinds of filtration devices.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…71 Although estimates of the infectious titer of blood from patients with vCJD are low 71,72 it has been demonstrated that blood and components from asymptomatic individuals appear capable of transmitting vCJD-infection following blood transfusion. Major efforts have been made toward the development of screening assays and diagnostic tests for vCJD in blood [72][73][74][75] ; the development and implementation of prion reduction filters [76][77][78][79][80] ; understanding the numbers of individuals who may be sub-clinically affected with vCJD 39,[81][82][83][84] and what this really means in terms of further spread of vCJD. There are significant challenges to be faced in each of these areas, which are further confounded by the absence of an available treatment for vCJD.…”
Section: Blood As a Route Of Transmission Of Vcjdmentioning
confidence: 99%